RETRACTED: Russian-Kazakh border: Sustainability and typology by ethnic, historical and natural characteristics - Sokolov Aleksandr; Rudneva Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001